2017 IEEE 56th Annual Conference on Decision and Control (CDC) 2017
DOI: 10.1109/cdc.2017.8263939
|View full text |Cite
|
Sign up to set email alerts
|

Aggregates of positive impulse response systems: A decomposition approach for complex networks

Abstract: Abstract-To simplify the analysis of complex dynamical networks, we have recently proposed an approach that decomposes the overall system into the sign-definite interconnection of subsystems with a Positive Impulse Response (PIR). PIR systems include and significantly generalise input-output monotone systems, and the PIR property (or equivalently, for linear systems, the Monotonic Step Response property) can be evinced from experimental data, without an explicit model of the system. An aggregate of PIR subsyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Although, the question of systems with positive impulse response (PIR) has been fairly well-discussed in the control theory literature [3537] the relation between imperfect adaptation (regulation) and PIR has not been well-explored. Drenstig et al (2008) first argued that a three protein network must contain at least one zero for adaptation i. e. to avoid, the system being PIR [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the question of systems with positive impulse response (PIR) has been fairly well-discussed in the control theory literature [3537] the relation between imperfect adaptation (regulation) and PIR has not been well-explored. Drenstig et al (2008) first argued that a three protein network must contain at least one zero for adaptation i. e. to avoid, the system being PIR [20].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it can be concluded that the network structures capable of adaptation should contain a non-PIR (NIR) impulse response. Further, Blanchini et al (2017) showed that if a linear, time-invariant LTI dynamical system h(t) contains a positive impulse response then it should satisfy the following where, H(jω) is the Fourier transform of h(t) [35].…”
Section: Methodsmentioning
confidence: 99%
“…well-discussed in the control theory literature [35][36][37] the relation between imperfect adaptation (regulation) and PIR has not been well-explored. Drenstig et al (2008) first argued that a three protein network must contain at least one zero for adaptation i. e. to avoid, the system being PIR [20].…”
Section: Definitionmentioning
confidence: 99%
“…1. The set of coupled, first-order differential equations in (35) constitute a well-posed dynamical system.…”
Section: Assumptionsmentioning
confidence: 99%